Pengaruh Pengeluaran Pemerintah di Sektor Pendidikan dan Kesehatan terhadap Indeks Pembangunan Manusia di Aceh - Salman; Rasyidin (Jurnal Samudra Ekonomika, 2020)
The study was conducted with the aim to determine the effect of education and health sector spending on the human development index. The data used are education and health sector expenditure data and the human development index from 2007-2017. Methods of data analysis using multiple linear regression equations. The results of multiple linear regression equations obtained Y = 66,9530 + 23,50261X1 + 43,22175 X2. The results of the determination coefficient test of 0,576 or 57,6% of the education sector expenditure variables and the health sector expenditure variables have an influence on the human development index. T-test results of education and health sector expenditure variables significantly influence the human development index. The simultaneous F test results in education sector expenditure and health sector expenditure have a significant effect on the human development index in Aceh Province.